2020
DOI: 10.1016/j.heliyon.2020.e05017
|View full text |Cite
|
Sign up to set email alerts
|

Digital images of pediatric mental disorders do not accurately represent the conditions

Abstract: Objective Digital images might contribute to stigma associated with mental disorders. The aim of this study was to investigate whether these images accurately represent pediatric mental disorders, as well as to explore specific image-related factors that influence perception. Methods Four hundred pictures were retrieved from three stock photograph websites (‘Shutterstock’, ‘iStock’ and ‘Adobe’) and ‘Google Images’ for mental disorders (ADHD, ASD, and depression) and som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…These results are consistent with a similar US study that includes more years of evaluation of print media (from 1985 to 2008) [ 12 ], where people diagnosed with ADHD are described in a generally positive light. However, more recent studies published in Belgium, analysing the written media [ 53 ] and pictures on the internet [ 54 ] show more negative results in the representation of ADHD patients. Such results with negative stereotypes about ADHD are worrying, given the fact that a recent study has shown negative self-views and depressive symptomatology as a mediator of functional difficulties at academic level in this population [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with a similar US study that includes more years of evaluation of print media (from 1985 to 2008) [ 12 ], where people diagnosed with ADHD are described in a generally positive light. However, more recent studies published in Belgium, analysing the written media [ 53 ] and pictures on the internet [ 54 ] show more negative results in the representation of ADHD patients. Such results with negative stereotypes about ADHD are worrying, given the fact that a recent study has shown negative self-views and depressive symptomatology as a mediator of functional difficulties at academic level in this population [ 55 ].…”
Section: Discussionmentioning
confidence: 99%